2023
DOI: 10.1186/s42234-023-00113-6
|View full text |Cite|
|
Sign up to set email alerts
|

Neuromodulation for recovery of trunk and sitting functions following spinal cord injury: a comprehensive review of the literature

Abstract: Trunk stability is crucial for people with trunk paralysis resulting from spinal cord injuries (SCI), as it plays a significant role in performing daily life activities and preventing from fall-related accidents. Traditional therapy used assistive methods or seating modifications to provide passive assistance while restricting their daily functionality. The recent emergence of neuromodulation techniques has been reported as an alternative therapy that could improve trunk and sitting functions following SCI. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…TSCS has been used in conjunction with locomotor training, robotic-assisted training and treadmill training to improve gait and locomotion in people with iSCI [12,13,23]. It has been reported that the combined intervention of stimulation and task-based activity could produce better results [21]. The current study aimed to investigate the effects of augmenting ABT to TSCS treatment on enhancing specific lower limb muscle strength and improving locomotor ability in an individual with chronic iSCI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TSCS has been used in conjunction with locomotor training, robotic-assisted training and treadmill training to improve gait and locomotion in people with iSCI [12,13,23]. It has been reported that the combined intervention of stimulation and task-based activity could produce better results [21]. The current study aimed to investigate the effects of augmenting ABT to TSCS treatment on enhancing specific lower limb muscle strength and improving locomotor ability in an individual with chronic iSCI.…”
Section: Introductionmentioning
confidence: 99%
“…Transcutaneous spinal cord electrical stimulation (TSCS) is an emerging treatment with promising outcomes to improve motor function beyond conventional therapy in people with chronic SCI [3]. It is a non-invasive method that uses superficial skin electrodes placed over the spinous processes [1,21]. TSCS could modulate post-SCI motor function [22].…”
Section: Introductionmentioning
confidence: 99%
“…This type of control is convenient when motions are repetitive and not subject to changing external or internal factors but is inappropriate when disturbances that can affect the desired motion are applied to the system. For this reason, feedback control of FNS to compensate for such perturbations has become a prominent topic of interest in research regarding seated trunk stability [ 12 ].…”
Section: Introductionmentioning
confidence: 99%